The Structural and Functional Capacity of Ruminal and Cecal Microbiota in Growing Cattle Was Unaffected by Dietary Supplementation of Linseed Oil and Nitrate - Popova, Milka; McGovern, Emily; McCabe, Matthew S.; Martin, Cécile; Doreau, Michel; Arbre, Marie; Meale, Sarah J.; Morgavi, Diego P.; Waters, Sinéad M. (Frontiers in Microbiology, 2017)
Microorganisms in the digestive tract of ruminants differ in their functionality and ability to use feed constituents. While cecal microbiota play an important role in post-rumen fermentation of residual substrates undigested in the rumen, limited knowledge exists regarding its structure and function. In this trial we investigated the effect of dietary supplementation with linseed oil and nitrate on methane emissions and on the structure of ruminal and cecal microbiota of growing bulls. Animals were allocated to either a CTL (control) or LINNIT (CTL supplemented with 1.9% linseed and 1.0% nitrates) diet. Methane emissions were measured using the GreenFeed system. Microbial diversity was assessed using amplicon sequencing of microbial genomic DNA. Additionally, total RNA was extracted from ruminal contents and functional mcrA and mtt genes were targeted in amplicon sequencing approach to explore the diversity of functional gene expression in methanogens. LINNIT had no effect on methane yield (g/kg DMI) even though it decreased methane production by 9% (g/day; P<0.05). Methanobrevibacter- and Methanomassiliicoccaceae-related OTUs were more abundant in cecum (72% and 24%) compared to rumen (60% and 11%) irrespective of the diet (P<0.05). Feeding LINNIT reduced the relative abundance of Methanomassiliicoccaceae mcrA cDNA reads in the rumen. Principal component analysis revealed significant differences in taxonomic composition and abundance of bacterial communities between rumen and cecum. Treatment decreased the relative abundance of a few Ruminococcaceae genera, without affecting global bacterial community structure. Our research confirms a high level of heterogeneity in species composition of microbial consortia in the main gastrointestinal compartments where feed is fermented in ruminants. There was a parallel between the lack of effect of LINNIT on ruminal and cecal microbial community structure and functions on one side and methane emission changes on the other. These results suggest that the sequencing strategy used here to study microbial diversity and function accurately reflected the absence of effect on methane phenotypes in bulls treated with linseed plus nitrate.